Effect of gas pressure and temperature on the regimes of liquid droplet collisions - Tkachenko P. P. Pavel Petrovich; Islamova A. G. Anastasiya Gomilievna; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen